The Boma: How containing COVID-19 also hurt the world's poorest farmers - International Livestock Research Institute (International Livestock Research Institute, 2022)
Many countries locked down in the burgeoning COVID-19 pandemic, trying to protect the public from infections and illness. But a new wave of research is examining how containment measures came with costs, too. Particularly for the 1 in 12 people in the world who are also smallholder farmers, responsible for producing most of the food in low- or middle-income countries. Brenda Coromina and Elliot Carleton hear from ILRI scientist Jim Hammond, whose team interviewed nearly 10,000 farmers across nine low-income countries. Hammond reveals the lasting effect of pandemic restrictions on these farmers, and what countries need to do in the future to shield these farmers from falling into crisis.